Power Garima-Rayleigh distribution: properties and applications - Thiamsorn, Issaraporn; Tanprayoon, Ekapak; Aryuyuen, Sirinapa (Journal of Applied Statistics and Information Technology, 2023)
In this paper, we have considered a new lifetime model of the class of power Garima generalized models, called the power Garima-Rayleigh (PG-R) distribution. Some statistical properties are provided, including quantile function, hazard function, moments, and order statistics. The maximum likelihood estimation is used to estimate the parameters of the PG-R distribution. In addition, we apply the PG-R distribution with two real-life data sets. The study found that the PG-R distribution is a model that describes the probability distribution of observation values close to the real data. The proposed distribution is more flexible and comprehensive with lifetime data than other related distributions, such as the Rayleigh, power Garima-Lindley, and Lindley distributions.